Implementing Electronic Forms for Prescription Screening during Pregnancy in Outpatient Obstetric Clinic - Lisa Aditama; Nur Khofifah (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Prescription screening is an assessment of the suitability of a prescription performed by a pharmacist to minimize medication errors. Numerous drugs can cross the placenta; therefore, caution is required when using medications during pregnancy. Objective: This study aimed to determine the problems of prescribing based on administrative, pharmaceutical, and clinical requirements using electronic forms and to analyze drug safety during pregnancy using electronic prescription archives from the outpatient obstetric clinic. Methods: This research employed an observational study utilized quantitative methods and retrospective data collection. The analysis focused on descriptive statistics to summarize and interpret the data according to the Pharmaceutical Care Standard in hospitals. Results: Administrative problems included the absence of a digital signature from the prescriber, patient weight, and allergy history in 100 electronic prescriptions (100%). Pharmaceutical requirement problems included the absence of dosage strength (8.00%) and unclear usage rules (9.00%). Clinical considerations included indications for drug selection (8%), potential drug interactions (3.00%), dose appropriateness (3.00%), duplication (2.00%), and contraindications (6.00%). Based on drug safety in pregnant women, 40 types of drugs were identified as category A drugs (7.50%), category B (32.50%), category C (50.00%), off-label (2.50%), and unknown (7.50%). Conclusion: Electronic prescription screening, which uses digital forms to review prescriptions, is a tool developed to improve patient safety by efficiently identifying potential drug therapy problems. The system accommodates structured screening based on specific criteria, such as pregnancy category and potential drug interactions, which helps prevent errors and ensures appropriate medication use.